Savoir et valeur. Pour une conception émancipatrice des « Éducations à » - Michel Fabre (Éducation et Socialisation)
In french curriculum, the PSHE (Personal Social and Health Education) seem to import values’ considerations beyond traditional knowledge. That is controversial. But this weberian dualism (facts versus values) must be critiqued. From Habermas, every knowledge is linked to human interests and, in the other hand, you can discuss about values and critic them with rational arguments. This paper is trying to show that Habermas’ thinking guide the PSHE, despite of their ambiguities, to emancipatory goals. Their meanings would be to support the democratization movement, and his communicational interest, which, in contemporary societies, put up technocratic management of problems mistaking politics for expertise. This perspective criticizes postmodern relativism that often supports the PSHE. That thereby regains Enlightenment and Condorcet’s thinking.